High density, low loss rare earth permanent magnet powder, bonded magnets and their manufacturing method

A high-density, low-loss rare earth permanent magnet powder with enhanced magnetic properties and uniform particle size distribution addresses the limitations of existing NdFeB magnets, enabling their use in high-speed and high-efficiency applications by improving density and thermal stability.

JP2025512118AActive Publication Date: 2025-04-16NINGXIA MAGVALLEY NOVEL MATERIALS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2025503021
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-14
Filing Date
2022-04-15
Publication Date
2025-04-16
Estimated Expiration
2042-04-15

AI Technical Summary

Technical Problem

Existing rare earth permanent magnet materials, such as NdFeB, face limitations in magnetic properties, high cost due to heavy rare earth element usage, and complex manufacturing processes, making them unsuitable for high-speed and high-efficiency applications in motors and other fields.

Method used

Development of a high-density, low-loss rare earth permanent magnet powder with a molecular formula Sm_x Fe_100-x-y-z M_y I_z, where M is a 3d or 4d transition metal, and I is an interstitial atom, combined with a manufacturing process involving rapid solidification and gas-solid reaction to achieve a maximum magnetic energy product of 36.299 MGOe and a compressed density of 5.5 g/cm^3, along with a uniform particle size distribution.

Benefits of technology

The new magnet powder enhances magnetic properties, reduces manufacturing costs, and enables successful application in conventional commercial environments by improving density, coercivity, and thermal stability, while maintaining high magnetic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025512118000001
    Figure 2025512118000001
  • Figure 2025512118000002
    Figure 2025512118000002
  • Figure 2025512118000003
    Figure 2025512118000003
Patent Text Reader

Abstract

The present invention provides a high density, low loss rare earth permanent magnet powder, a bonded magnet, and a method for producing the same. The molecular formula of the high density rare earth permanent magnet powder is Sm x Fe 100-x-y-z M y I z (wherein 6.0≦x≦9.5, 0≦y≦13, 1≦z≦15.2, M is a 3d transition metal and / or a 4d transition metal, and I is an interstitial atom, including N or a combination of N and H.) The high density rare earth permanent magnet powder has a maximum magnetic energy product of 36.299 MGOe or more and a compressed density of 5.5 g / cm. 3 The rare earth permanent magnet powder in the embodiment of the present invention has better overall properties than conventional rare earth permanent magnet powder, and can further improve the magnetic properties, increase the density of the magnetic powder, and make the particle size distribution of the magnetic powder more uniform.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to a Chinese patent application filed on April 14, 2022, with application number 202210392476.9, entitled "High density rare earth permanent magnet powder and manufacturing method thereof," and a Chinese patent application filed on April 14, 2022, with application number 202210386759.2, entitled "High density, low loss rare earth permanent magnet material and manufacturing method thereof," the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a magnetic material, in particular to a high-density, low-loss rare earth permanent magnet powder, a method for manufacturing high-density, low-loss rare earth permanent magnet powder, a high-density, low-loss rare earth bonded magnet, and a method for manufacturing a high-density, low-loss rare earth bonded magnet. [Background technology]

[0003] Since the 1970s and 1980s, rare earth permanent magnetic materials have been considered by industry as key materials in high-tech applications related to the interconversion of magnetic, electrical, and mechanical energy, with magnetic energy densities several times higher than those of conventional magnetic materials without rare earth components. Rare earth permanent magnetic materials are a general term for a family of intermetallic compounds, usually formed by rare earth transition metals and other metals or nonmetals, which can form permanent magnetic materials with various phase structures and potential application values ​​depending on the combination of components.

[0004] So far, the commercially available rare earth permanent magnet materials are mainly NdFeB produced by sintering and adhesion processes. With the development trend of smaller, lighter, higher frequency and higher speed of downstream motor products, NdFeB materials have gradually become unable to keep up with the upgrading and development of downstream industries due to factors such as magnetic properties reaching the theoretical limit, large eddy current loss and complicated molding process. In addition, NdFeB is usually added with heavy rare earth elements during production, which makes it expensive, and the cost fluctuates greatly due to market factors, so the cost performance advantage is not high.

[0005] In general, rare earth permanent magnet materials are mainly used in high-end motor fields such as high-frequency and high-speed motors, as well as in high-performance micro-motors, special-shape motors, sensors, and other fields, covering strategic emerging fields such as new energy automobiles, energy-saving and environmentally friendly frequency conversion home appliances, and intelligent manufacturing industry. For example, in the automotive field, rare earth permanent magnet materials are tested in automotive wipers, electronic throttles, blowers, batteries, refrigeration fans, sunroofs, power steering, electric air conditioners, fuel tank cap opening and closing, electric windows, doors, seat adjustments, pre-collision, electric braking systems, and other automotive parts.

[0006] The rapid development of permanent magnet drive motors for new energy vehicles will lead to ever higher peak speeds. This requires motors that can achieve higher energy efficiency, smaller size, and lower cost in this high-speed environment. Rare earth bonded magnets are required to have better overall properties. However, existing rare earth bonded magnets often only have excellent magnetic properties, and other properties do not have significant advantages, and as a result, existing rare earth bonded magnets cannot be successfully applied to existing commercial application environments. Summary of the Invention [Problem to be solved by the invention]

[0007] The technical problem to be solved by the present application is to provide a high density, low loss rare earth permanent magnet powder, a manufacturing method for high density, low loss rare earth permanent magnet powder, a high density, low loss rare earth bonded magnet, and a manufacturing method for a high density, low loss rare earth bonded magnet, which improve the comprehensive properties of rare earth bonded magnets and enable the rare earth bonded magnets to be successfully applied in conventional commercial application environments. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention provides a compound having the molecular formula Sm x Fe 100-x-y-z My I z (wherein 6.0≦x≦9.5, 0≦y≦13, 1≦z≦15.2, M is a 3d transition metal and / or a 4d transition metal, and I is an interstitial atom, including N or a combination of N and H), the maximum magnetic energy product is 36.299 MGOe or more, and the compressed density is 5.5 g / cm 3 The present invention provides a high density rare earth permanent magnet powder as described above.

[0009] Optionally, the 3d transition metal and / or 4d transition metal comprises one or more of Ti, V, Cr, Mn, Co, Ni, Cu, Zn, Zr, Nb, Mo.

[0010] Optionally, the high density rare earth permanent magnet powder has a particle size of 0.6 μm≦x10≦0.92 μm, 2 μm≦x50≦2.55 μm, or 5.93 μm≦x99≦8.1 μm.

[0011] Optionally, the high density rare earth permanent magnet powder has a remanent magnetic induction strength of 14.289 kGs or more and an intrinsic coercivity of 10.255 kOe or more.

[0012] Optionally, the high density rare earth permanent magnet powder has a weight increase rate of less than 3.2% when subjected to thermogravimetric analysis at 400° C. in an air atmosphere.

[0013] The present invention also provides obtaining a raw material, the raw material containing Sm, Fe, and a 3d transition metal and / or a 4d transition metal, the ratio of Sm, Fe, and the 3d transition metal and / or the 4d transition metal in the raw material being the same as the ratio of each element in the high density rare earth permanent magnet powder; producing a samarium-iron master alloy using the raw material; samarium- Iron alloy The samarium-iron-nitrogen alloy Sm is produced by gas-solid reaction with nitrogen or a mixture of nitrogen and hydrogen. x Fe 100-x-y-z M y I z forming a and grinding the samarium-iron-nitrogen alloy to obtain the high density rare earth permanent magnet powder.

[0014] Optionally, the step of producing a samarium-iron master alloy using the raw material further comprises: The method includes the step of producing a samarium-iron master alloy using the raw materials by rapid solidification flake technology.

[0015] Optionally, in the step of using the raw material to produce a samarium-iron master alloy by a rapid solidification flake technique, the rotation speed of the rapid solidification roll is 50-80 m / s, and the thickness of the produced samarium-iron master alloy is less than 1 mm.

[0016] Optionally, in the gas-solid reaction process, the reaction temperature is 400-800° C., the reaction time is 1-200 hours, and the pressure is 0.1-2.0 MPa.

[0017] Optionally, in the polishing process, the total energy output is 60-80 KJ.

[0018] The present invention also provides a high density, low loss rare earth bonded magnet, comprising a high density rare earth permanent magnet powder, an adhesive, and a processing aid.

[0019] Optionally, the adhesive comprises at least one of chlorinated polyethylene, polyamide resin, thermoplastic polyimide, liquid crystal polymer, polyphenylene sulfide, polyphenylene ether, polyolefin, modified polyolefin, polycarbonate, polymethyl methacrylate, polyether, polyether ketone, polyetherimide, polyformaldehyde, chlorosulfonated polyethylene, and / or at least one of copolymers, blends, and polymer alloys formed with at least one of chlorinated polyethylene, polyamide resin, thermoplastic polyimide, liquid crystal polymer, polyphenylene sulfide, polyphenylene ether, polyolefin, modified polyolefin, polycarbonate, polymethyl methacrylate, polyether, polyether ketone, polyetherimide, polyformaldehyde, and chlorosulfonated polyethylene.

[0020] Optionally, the adhesive comprises a thermoplastic elastomer.

[0021] Optionally, the processing aid comprises at least one of a coupling agent, a plasticizer, a lubricant, and a flame retardant.

[0022] Optionally, the coupling agent comprises a titanate-based coupling agent and / or a silane-based coupling agent.

[0023] Optionally, the plasticizer comprises at least one of dioctyl phthalate DOP, stearates, fatty acids, phosphoric acid esters, benzene polycarboxylic acid esters, and alkyl sulfonic acid esters.

[0024] Optionally, the lubricant comprises at least one of silicone oil, wax, fatty acid, oleic acid, polyester, synthetic ester, carboxylic acid, alumina, silica, titanium dioxide.

[0025] The present invention also provides Mixing high density rare earth permanent magnet powder, an adhesive, and a processing aid to obtain a mixture; and processing the mixture by an extrusion or injection molding process in an environment where the magnetic field orientation exceeds 8 kOe to produce a high density, low loss rare earth bonded magnet.

[0026] Optionally, the step of processing the mixture by an extrusion or injection molding process in a magnetic field orientation environment exceeding 8 kOe to produce a high density, low loss rare earth bonded magnet comprises: When an extrusion molding process is used, the steps include kneading the mixture in a kneader, heating the mixture to melt it, then injecting it into a single screw extruder with a magnetic field orientation exceeding 8 kOe, extruding it through the single screw extruder, and then cooling and molding it to obtain a high density, low loss rare earth bonded magnet.

[0027] Optionally, the step of processing the mixture by an extrusion or injection molding process in a magnetic field orientation environment exceeding 8 kOe to produce a high density, low loss rare earth bonded magnet comprises: When using an injection molding process, the mixture is produced as mixed pellets in a twin screw extruder; and heating the mixed pellets to melt them, and then injecting them into an injection molding machine with a magnetic field orientation exceeding 8 kOe to obtain a high density, low loss rare earth bonded magnet. Effect of the Invention

[0028] Compared with the prior art, the present application includes the following advantages:

[0029] The rare earth permanent magnet powder in the embodiment of the present invention has good comprehensive properties, further improves the magnetic properties, increases the density of the magnetic powder, and makes the particle size distribution of the magnetic powder more uniform, compared with the conventional rare earth permanent magnet powder. The application of this rare earth permanent magnet powder to rare earth permanent magnet materials can effectively improve the comprehensive properties of the rare earth permanent magnet materials, and enable the rare earth bonded magnets to be successfully applied in the conventional commercial application environment.

[0030] As for the high density and low loss rare earth bonded magnet of the embodiment of the present invention, high density rare earth permanent magnet powder is used to manufacture the high density and low loss rare earth bonded magnet. The high density rare earth permanent magnet powder further improves the magnetic properties, increases the density of the magnetic powder, and makes the particle size distribution of the magnetic powder more uniform. The application of this rare earth permanent magnet powder to the rare earth bonded magnet effectively improves the comprehensive properties of the rare earth bonded magnet, and also reduces the requirements for the magnetic field strength from the manufacturing process of the rare earth bonded magnet, thereby reducing the manufacturing cost of the rare earth bonded magnet to a certain extent, and enabling the rare earth bonded magnet to be successfully applied in the traditional commercial application environment.

[0031] The above description is only an outline of the technical solution of the present application. In order to more clearly understand the technical solution of the present application, the following provides specific embodiments of the present application, which can be implemented in accordance with the contents of the specification, and in order to make the above and other objectives, features and advantages of the present application more clearly understandable. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] In order to make the objectives, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the drawings in the embodiments of the present application, but it is clear that the described embodiments are only a part of the embodiments of the present application, and are not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0033] The present invention relates to a compound having the molecular formula Sm x Fe 100-x-y-z M y I z (wherein 6.0≦x≦9.5, 0≦y≦13, 1≦z≦15.2, M is a 3d transition metal and / or a 4d transition metal, and I is an interstitial atom, including N or a combination of N and H.) The maximum magnetic energy product is 36.299 MGOe or more, and the compressed density is 5.5 g / cm 3 Thus, a high density rare earth permanent magnet powder is disclosed.

[0034] Specifically, the high density rare earth permanent magnet powder produced by the present invention does not use heavy rare earth metals, and the composition of the high density rare earth permanent magnet powder is reasonably controlled. Through a specific synthesis method, the final high density rare earth permanent magnet powder has a maximum magnetic energy product of 36.299 MGOe or more and a compressed density of 5.5 g / cm. 3 This is the end of the invention. The magnetic properties are maintained at a high level, the compressed density is effectively improved, and the overall properties of the high density rare earth permanent magnet powder are improved.

[0035] Optionally, the 3d transition metal and / or 4d transition metal comprises one or more of Ti, V, Cr, Mn, Co, Ni, Cu, Zn, Zr, Nb, Mo.

[0036] Optionally, the high density rare earth permanent magnet powder has a particle size of 0.6 μm≦x10≦0.92 μm, 2 μm≦x50≦2.55 μm, or 5.93 μm≦x99≦8.1 μm.

[0037] Specifically, the present invention uses a specific synthesis method to ensure a wide particle size distribution while improving the compaction density, thereby reducing the loss after powder compaction and improving the comprehensive properties of the rare earth permanent magnet material produced later.

[0038] Optionally, the high density rare earth permanent magnet powder has a remanent magnetic induction strength of 14.289 kGs or more and an intrinsic coercivity of 10.255 kOe or more.

[0039] Specifically, the high density rare earth permanent magnet powder of the present invention has a high magnetic energy product, so that the energy that can be converted is more. It also has high residual magnetic induction strength and intrinsic coercivity. When the residual magnetic induction strength and intrinsic coercivity are high, the magnet has high anti-demagnetization ability and high magnetic field strength, so that the high density rare earth permanent magnet powder can be widely used in the fields of household appliances, new energy automobiles, wind turbines, industrial motors and the like.

[0040] Optionally, the high density rare earth permanent magnet powder has a weight increase rate of less than 3.2% when subjected to thermogravimetric analysis at 400° C. in an air atmosphere.

[0041] Specifically, if the weight gain rate is low in the thermogravimetric analysis of the high-density rare earth permanent magnet powder, the high-density rare earth permanent magnet powder has high thermal stability and can retain its inherent properties as much as possible even in high-temperature environments, and is suitable for a variety of application environments.

[0042] The present invention also provides obtaining a raw material, the raw material containing Sm, Fe, and a 3d transition metal and / or a 4d transition metal, the ratio of Sm, Fe, and the 3d transition metal and / or the 4d transition metal in the raw material being the same as the ratio of each element in the high density rare earth permanent magnet powder; producing a samarium-iron master alloy using the raw material; samarium- Iron alloy The samarium-iron-nitrogen alloy Sm is produced by gas-solid reaction with nitrogen or a mixture of nitrogen and hydrogen. x Fe 100-x-y-z M y I z forming a and grinding the samarium-iron-nitrogen alloy to obtain the high density rare earth permanent magnet powder.

[0043] Specifically, the polishing process for the samarium-iron-nitrogen alloy may be performed by jet milling and / or ball milling, among which jet milling crushes coarse particles by repeated collision and friction caused by the intersection of multiple high-pressure air streams, and the required powder grain size can be obtained by controlling the polishing pressure and the speed of the sorting machine.

[0044] Optionally, the step of producing a samarium-iron master alloy using the raw material further comprises: The method includes the step of producing a samarium-iron master alloy using the raw materials by rapid solidification flake technology.

[0045] Specifically, samarium- Iron alloy Rapid solidification technology is used to manufacture. Compared with traditional smelting technologies such as arc melting and ingot casting, the cooling rate of the molten metal is faster and the distribution of the crystal phase is more uniform. The average grain size of the grain distribution of the rapidly solidified ribbon produced by this method is less than 8μm, which is favorable for the diffusion of nitrogen atoms and the control of grain size distribution in the subsequent steps.

[0046] Optionally, in the step of using the raw material to prepare the samarium-iron master alloy by the rapid solidification flake technique, the rotation speed of the rapid solidification roll is 50-80 m / s, and the thickness of the prepared samarium-iron master alloy is less than 1 mm. By rationally controlling the rotation speed of the rapid solidification roll, the precipitation of the crystal phase can be effectively suppressed in the preparation process, and the occurrence of crystal aggregation can be avoided. The width of the main phase columnar crystal decreases with the decrease in the thickness of the sheet. When the thickness of the sheet is small, a large amount of polycrystalline particles and ultrafine powders are easily generated when the sheet is powdered, so that a high-density permanent magnet powder with good comprehensive properties is easily obtained.

[0047] Optionally, in the gas-solid reaction process, the reaction temperature is 400-800°C, the reaction time is 1-200 hours, and the pressure is 0.1-2.0 MPa. Rationally controlling the reaction conditions in the above gas-solid reaction process can facilitate the formation of good crystalline phase, and facilitate the production of high density permanent magnet powder with good particle size distribution in the subsequent treatment process.

[0048] Optionally, the total energy output in the grinding process is 60-80KJ. By rationally controlling the energy output in the grinding process, the produced high density permanent magnet powder has better particle size distribution and higher intrinsic coercivity.

[0049] The demagnetization process of single crystal samarium-iron-nitrogen magnetic powder is characterized by a nucleation mechanism, and the remanence and coercivity of the magnetic powder change with the change in the size of the magnetic powder particles. Previous processes have focused on magnetic properties, but often ignored the actual needs and effects in application processes. By controlling the powdering parameters and energy range, a high-density permanent magnetic powder with high magnetic properties and suitable for downstream magnet manufacturing can be obtained. This high-density permanent magnetic powder does not only focus on the level of a single magnetic property, but on the basis of the saturation magnetization strength and magnetocrystalline anisotropy field from the previous process, improves the comprehensive properties of the magnetic powder, ensures a wide particle size distribution, increases the compaction density and coercivity, and reduces the loss of magnetic powder after molding. The produced high-density permanent magnetic powder has a maximum magnetic energy product of more than 40 MGOe, a remanence of more than 14.7 kGs, an intrinsic coercivity of more than 11 kOe, and a TG weight gain (@400℃, air atmosphere) of ≦3.2%.

[0050] As one possible embodiment of the present invention, after the high density permanent magnet powder is produced, the magnet may be subjected to a surface treatment to further improve the oxidation resistance of the magnetic powder and the rotation effect of the magnetic powder in the magnetic field formation process, and lay the foundation for producing high density and low loss magnets.

[0051] Specifically, the surface treatment agent and the high density permanent magnet powder may be dissolved in a mixed solvent containing alcohols and ketones, and the surface of the high density permanent magnet powder may be coated with the surface treatment agent.

[0052] Here, the surface treatment agent may be a coupling agent such as titanate or silane, which can prevent oxidation of the magnetic powder in the subsequent processes and improve dispersibility and adhesion, and is advantageous for producing a permanent magnet material with excellent properties.

[0053] The present invention provides a high density, low loss rare earth bonded magnet comprising a high density rare earth permanent magnet powder, an adhesive, and a processing aid.

[0054] Specifically, the high-density rare earth permanent magnet powder of the present invention ensures a wide particle size distribution while improving the compressed density and reducing powder loss after molding, thereby improving the overall characteristics of the rare earth bonded magnet produced later.

[0055] In addition, the high density rare earth permanent magnet powder has a high magnetic energy product, can store more energy, and has high residual magnetic induction strength and intrinsic coercivity. When the residual magnetic induction strength and intrinsic coercivity are high, the magnet has high demagnetization resistance and high magnetic field strength, so that the high density rare earth permanent magnet powder can be widely used in fields such as household appliances, new energy automobiles, wind turbines, industrial motors, etc.

[0056] If the thermogravimetric analysis of the high density rare earth permanent magnet powder shows a low weight gain rate, the high density rare earth permanent magnet powder has high thermal stability and can retain its inherent properties as much as possible even in high temperature environments, making the high density rare earth permanent magnet powder suitable for various application environments.

[0057] As one possible embodiment of the present invention, after producing the high density permanent magnet powder, the magnet may be subjected to surface treatment to further improve the oxidation resistance of the magnetic powder and the rotation effect of the magnetic powder in the magnetic field forming process, and lay the foundation for producing high density and low loss magnets.

[0058] Specifically, the surface treatment agent and the high density permanent magnet powder may be dissolved in a mixed solvent containing alcohols and ketones, and the surface of the high density permanent magnet powder may be coated with the surface treatment agent.

[0059] Here, the surface treatment agent may be a coupling agent such as titanate or silane, which can prevent oxidation of the magnetic powder in subsequent processes and improve dispersibility and adhesion, and is advantageous for producing a bonded magnet with excellent properties.

[0060] Optionally, the adhesive comprises at least one of chlorinated polyethylene, polyamide resin, thermoplastic polyimide, liquid crystal polymer, polyphenylene sulfide, polyphenylene ether, polyolefin, modified polyolefin, polycarbonate, polymethyl methacrylate, polyether, polyether ketone, polyetherimide, polyformaldehyde, chlorosulfonated polyethylene, and / or at least one of copolymers, blends, and polymer alloys formed with at least one of chlorinated polyethylene, polyamide resin, thermoplastic polyimide, liquid crystal polymer, polyphenylene sulfide, polyphenylene ether, polyolefin, modified polyolefin, polycarbonate, polymethyl methacrylate, polyether, polyether ketone, polyetherimide, polyformaldehyde, and chlorosulfonated polyethylene.

[0061] Among them, the polyamide resin may include, for example, nylon 6, nylon 46, nylon 66, nylon 610, nylon 612, nylon 11, nylon 12, nylon 6-12, nylon 6-66, etc. The liquid crystal polymer may be aromatic polyester, etc. The polyolefin may be polyethylene, polypropylene, etc.

[0062] Optionally, the adhesive comprises at least one of thermoplastic elastomers, such as styrenes (SBS, SIS, SEBS, SEPS), alkenes (TP0, TPV), dienes (TPB, TPI), vinyl chlorides (TPVC, TCPE), urethanes (TPU), esters (TPEE), amides (TPAE), organic fluorines (TPF), silicones, and ethylenes.

[0063] Specifically, the adhesive improves the flowability of the magnetic powder particles and the bond strength between them, and provides the magnet with mechanical properties and corrosion resistance. The type of adhesive used depends on the molding process and the needs of use, and materials with high bond strength, high adhesive strength, low water absorption, and excellent dimensional stability may be used as the adhesive.

[0064] For example, when the high density, low loss rare earth bonded magnet to be manufactured is a bonded magnet, the adhesive may be at least one of chlorinated polyethylene, polyamide resin, thermoplastic polyimide, liquid crystal polymer, polyphenylene sulfide, polyphenylene ether, polyolefin, modified polyolefin, polycarbonate, polymethyl methacrylate, polyether, polyether ketone, polyetherimide, polyformaldehyde, and chlorosulfonated polyethylene, and / or at least one of copolymers, blends, and polymer alloys formed with at least one of chlorinated polyethylene, polyamide resin, thermoplastic polyimide, liquid crystal polymer, polyphenylene sulfide, polyphenylene ether, polyolefin, modified polyolefin, polycarbonate, polymethyl methacrylate, polyether, polyether ketone, polyetherimide, polyformaldehyde, and chlorosulfonated polyethylene.

[0065] When the high density, low loss rare earth bonded magnet to be manufactured is a magnetic elastomer, the adhesive may be a thermoplastic elastomer, and further, according to actual needs, at least one of chlorinated polyethylene, polyamide resin, thermoplastic polyimide, liquid crystal polymer, polyphenylene sulfide, polyphenylene ether, polyolefin, modified polyolefin, polycarbonate, polymethyl methacrylate, polyether, polyether ketone, polyetherimide, polyformaldehyde, chlorosulfonated polyethylene, and / or at least one of copolymers, blends, and polymer alloys formed with at least one of chlorinated polyethylene, polyamide resin, thermoplastic polyimide, liquid crystal polymer, polyphenylene sulfide, polyphenylene ether, polyolefin, modified polyolefin, polycarbonate, polymethyl methacrylate, polyether, polyether ketone, polyetherimide, polyformaldehyde, chlorosulfonated polyethylene.

[0066] Optionally, the processing aids include at least one of a coupling agent, a plasticizer, a lubricant, and a flame retardant, so as to further improve the overall properties of the high density, low loss rare earth bonded magnet.

[0067] Optionally, the coupling agent comprises a titanate-based coupling agent and / or a silane-based coupling agent, which can effectively improve the binding effect between the magnetic powder and the adhesive, and also effectively promote the improvement of the orientation factor of the powder particles in the magnetic field.

[0068] Optionally, the plasticizer comprises at least one of dioctyl phthalate DOP, stearates, fatty acids, phosphoric acid esters, benzene polycarboxylic acid esters, and alkyl sulfonic acid esters.

[0069] Optionally, the lubricant comprises at least one of silicone oil, wax, fatty acid, oleic acid, polyester, synthetic ester, carboxylic acid, alumina, silica, and titanium dioxide. The plasticizer and lubricant can improve the properties of the high density and low loss rare earth bonded magnet, and can simplify the processing conditions to a certain extent and improve the processing efficiency.

[0070] Optionally, the flame retardant includes organic flame retardants, inorganic flame retardants, halogen-based flame retardants (organic chlorides and organic bromides), non-halogen flame retardants, etc. Organic flame retardants include bromine-based, phosphorus-nitrogen-based, nitrogen-based, red phosphorus and compound-based flame retardants, and inorganic flame retardants include antimony trioxide, magnesium hydroxide, aluminum hydroxide, silicon-based and other flame retardants.

[0071] The present invention also provides Mixing high density rare earth permanent magnet powder, an adhesive, and a processing aid to obtain a mixture; and processing the mixture by an extrusion or injection molding process in an environment where the magnetic field orientation exceeds 8 kOe to produce a high density, low loss rare earth bonded magnet.

[0072] Specifically, due to the good particle size distribution of high density rare earth permanent magnet powder, in the manufacturing process of high density, low loss rare earth bonded magnets, the magnetic field strength can be lower than the commonly required 13kOe, thereby reducing the manufacturing cost of rare earth bonded magnets to a certain extent, enabling rare earth bonded magnets to be successfully applied in traditional commercial application environments, and also giving the rare earth bonded magnets good comprehensive properties.

[0073] Optionally, processing the mixture by an extrusion or injection molding process in an environment where the magnetic field orientation exceeds 8 kOe to produce a high density, low loss rare earth bonded magnet comprises: When an extrusion molding process is used, the steps include kneading the mixture in a kneader, heating the mixture to melt it, then injecting it into a single screw extruder with a magnetic field orientation exceeding 8 kOe, extruding it through the single screw extruder, and then cooling and molding it to obtain a high density, low loss rare earth bonded magnet.

[0074] Specifically, when an extrusion molding process is used, the adhesive and processing aid may be added at a ratio of 4% to 30%.

[0075] Optionally, processing the mixture by an extrusion or injection molding process in an environment where the magnetic field orientation exceeds 8 kOe to produce a high density, low loss rare earth bonded magnet comprises: When using an injection molding process, the mixture is produced as mixed pellets in a twin screw extruder; and heating the mixed pellets to melt them, and then injecting them into an injection molding machine with a magnetic field orientation exceeding 8 kOe to obtain a high density, low loss rare earth bonded magnet.

[0076] Specifically, when using an injection molding process, the addition ratio of the adhesive and processing aid may be 5% to 30%. In the process of producing mixed pellets by a twin-screw extruder, the temperature may be controlled to 130°C to 350°C. In the process of injection molding in addition to an injection molding machine with a magnetic field orientation exceeding 8kOe, the temperature may be controlled between 190°C to 350°C.

[0077] The shape of the magnet can be manufactured into various three-dimensional shapes such as a tile shape, a cylinder shape, a ring shape, a square shape, a flat shape, etc. by selecting various molds according to actual needs, but the present invention is not limited thereto.

[0078] In order to enable those skilled in the art to better understand the present invention, the manufacturing method of the high density, low loss rare earth bonded magnet of the present invention will be described below using several specific examples.

[0079] Manufacturing high density rare earth permanent magnet powder

[0080] Example 1 The other raw material components, other than nitrogen, were mixed, which included the rare earth elements Sm, Fe, Co, and Nb, with the atomic percentages of the mixture being Sm 8.5%, Fe 76%, Co 8%, and Nb 5%.

[0081] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 50 m / s, and it took 10 hours to cool the sheet to room temperature, resulting in a sheet with a thickness of 0.5 mm and an average grain size of 7.5 μm in the crystal grain distribution. No annealing treatment was required.

[0082] The rapidly solidified flakes were subjected to a gas-solid reaction in a nitrogen atmosphere of 0.1 to 2.0 MPa at a reaction temperature of 400° C. for 1 hour.

[0083] The material treated in the above steps was ground in a ball mill for 5 hours, and the energy required for the grinding was 60 kJ.

[0084] Example 2 The other raw material components, other than nitrogen, were mixed, which included the rare earth elements Sm, Fe, Co, and Nb, with the atomic percentages of the mixture being Sm 8.5%, Fe 76%, Co 8%, and Nb 5%.

[0085] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 50 m / s, and it took 8 hours to cool the sheet to room temperature, resulting in a sheet with a thickness of 0.5 mm and an average grain size of 7.3 μm in the crystal grain distribution. No annealing treatment was required.

[0086] The rapidly solidified flakes were subjected to a gas-solid reaction at 400° C. for 150 hours in a nitrogen atmosphere of 0.1 to 2.0 MPa.

[0087] The material treated in the above steps was ground in a ball mill for 5 hours, and the energy required for the grinding was 60 kJ.

[0088] Example 3 The other raw material components, other than nitrogen, were mixed, which included the rare earth elements Sm, Fe, Co, and Nb, with the atomic percentages of the mixture being Sm 8.5%, Fe 76%, Co 8%, and Nb 5%.

[0089] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 80 m / s, and it took 10 hours to cool to room temperature, resulting in a sheet with a thickness of 0.4 mm and an average grain size of 6.9 μm in the crystal grain distribution. No annealing treatment was required.

[0090] The rapidly solidified flakes were subjected to a gas-solid reaction at 400° C. for 200 hours in a nitrogen atmosphere of 0.1 to 2.0 MPa.

[0091] The material treated in the above steps was ground in a ball mill for 5 hours, and the energy required for the grinding was 60 kJ.

[0092] Example 4 The other raw material components, other than nitrogen, were mixed, which included the rare earth elements Sm, Fe, Co, and Nb, with the atomic percentages of the mixture being Sm 8.5%, Fe 76%, Co 8%, and Nb 5%.

[0093] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 50 m / s, and it took 10 hours to cool the sheet to room temperature, resulting in a sheet with a thickness of 0.4 mm and an average grain size of 7.3 μm in the crystal grain distribution. No annealing treatment was required.

[0094] The rapidly solidified flakes were subjected to a gas-solid reaction at 600° C. for 150 hours in a nitrogen atmosphere of 0.1 to 2.0 MPa.

[0095] The material treated in the above steps was ground in a ball mill for 5 hours, and the energy required for the grinding was 60 kJ.

[0096] Example 5 The other raw material components, other than nitrogen, were mixed, which included the rare earth elements Sm, Fe, Co, and Nb, with the atomic percentages of the mixture being Sm 8.5%, Fe 76%, Co 8%, and Nb 5%.

[0097] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 50 m / s, and it took 8 hours to cool to room temperature, resulting in a sheet with a thickness of 0.4 mm and an average grain size of 7.3 μm in the crystal grain distribution. No annealing treatment was required.

[0098] The rapidly solidified flakes were subjected to a gas-solid reaction at 800° C. for 150 hours in a nitrogen atmosphere of 0.1 to 2.0 MPa.

[0099] The material treated in the above steps was ground in a ball mill for 6 hours, with the energy required for grinding being 65 kJ.

[0100] Example 6 The other raw material components, other than nitrogen, were mixed, which included the rare earth elements Sm, Fe, Co, and Nb, with the atomic percentages of the mixture being Sm 8.5%, Fe 76%, Co 8%, and Nb 5%.

[0101] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 50 m / s, and the time required for cooling to 40°C was 8 hours, resulting in a sheet with a thickness of 0.4 mm and an average grain size of 7.3 μm in the crystal grain distribution. No annealing treatment was required.

[0102] The rapidly solidified flakes were subjected to a gas-solid reaction at 600° C. for 60 hours in a nitrogen atmosphere of 0.1 to 2.0 MPa.

[0103] The material treated in the above steps was ground in a ball mill for 6 hours, and the energy required for the grinding was 70 kJ.

[0104] Example 7 Other raw material components than nitrogen were mixed, including the rare earth elements Sm, Fe, Ti, and Cr, with the atomic percentages of the mixture being Sm 6%, Fe 72.8%, Ti 3%, and Cr 3%.

[0105] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 50 m / s, and the time required for cooling to 40°C was 8 hours, resulting in a sheet with a thickness of 0.4 mm and an average grain size of 7.3 μm in the crystal grain distribution. No annealing treatment was required.

[0106] The rapidly solidified flakes were subjected to a gas-solid reaction at 600° C. for 60 hours in a nitrogen atmosphere of 0.1 to 2.0 MPa.

[0107] The material treated in the above steps was ground in a ball mill for 4 hours, and the energy required for the grinding was 80 kJ.

[0108] Example 8 Other raw material components than nitrogen were mixed, including the rare earth elements Sm, Fe, V, and Mn, with the atomic percentages of the mixture being Sm 6%, Fe 72.8%, V 3%, and Mn 3%.

[0109] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 50 m / s, and it took 10 hours to cool the sheet to room temperature, resulting in a sheet with a thickness of 0.5 mm and an average grain size of 7.5 μm in the crystal grain distribution. No annealing treatment was required.

[0110] The rapidly solidified flakes were subjected to a gas-solid reaction at 400° C. for 1 hour in a nitrogen atmosphere of 0.1 to 2.0 MPa.

[0111] The material treated in the above steps was ground in a ball mill for 5 hours, and the energy required for the grinding was 60 kJ.

[0112] Example 9 The other raw material components, other than nitrogen, were mixed, including the rare earth elements Sm and Fe, with the atomic percentage of the mixture being 9.5% Sm and 89.5% Fe.

[0113] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 50 m / s, and the time required for cooling to room temperature was 8 hours, resulting in a sheet with a thickness of 0.5 mm and an average grain size of 7.3 μm in the crystal grain distribution. No annealing treatment was required.

[0114] The rapidly solidified flakes were subjected to a gas-solid reaction at 400° C. for 150 hours in a nitrogen atmosphere of 0.1 to 2.0 MPa.

[0115] The material treated in the above steps was ground in a ball mill for 5 hours, and the energy required for the grinding was 60 kJ.

[0116] Example 10 Other raw material components than nitrogen were mixed, which included the rare earth elements Sm, Fe, Ni, and Mo, with the atomic percentages of the mixture being Sm 8.5%, Fe 76%, Ni 8%, and Mo 5%.

[0117] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 80 m / s, and it took 10 hours to cool to room temperature, resulting in a sheet with a thickness of 0.4 mm and an average grain size of 6.9 μm in the crystal grain distribution. No annealing treatment was required.

[0118] The rapidly solidified flakes were subjected to a gas-solid reaction at 400° C. for 200 hours in a nitrogen atmosphere of 0.1 to 2.0 MPa.

[0119] The material treated in the above steps was ground in a ball mill for 5 hours, and the energy required for the grinding was 60 kJ.

[0120] Example 11 Other raw material components than nitrogen were mixed, including the rare earth elements Sm, Fe, Cu, and Zn, with the atomic percentages of the mixture being Sm 8.5%, Fe 76%, Cu 8%, and Zn 5%.

[0121] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 50 m / s, and it took 8 hours to cool to room temperature, resulting in a sheet with a thickness of 0.4 mm and an average grain size of 7.3 μm in the crystal grain distribution. No annealing treatment was required.

[0122] The rapidly solidified flakes were subjected to a gas-solid reaction at 800° C. for 150 hours in a nitrogen atmosphere of 0.1 to 2.0 MPa.

[0123] The material treated in the above steps was ground in a ball mill for 6 hours, with the energy required for grinding being 65 kJ.

[0124] Example 12 The other raw material components, except for nitrogen, were mixed, which included the rare earth elements Sm, Fe, and Zr, with the atomic percentages of the mixture being 8.5% Sm, 76% Fe, and 13% Zr.

[0125] Using the above raw materials, samarium- Iron alloy The rotation speed of the quenching and solidification roll was 50 m / s, and the time required for cooling to 40°C was 8 hours, resulting in a sheet with a thickness of 0.4 mm and an average grain size of 7.3 μm in the crystal grain distribution. No annealing treatment was required.

[0126] The rapidly solidified flakes were subjected to a gas-solid reaction at 600° C. for 60 hours in a nitrogen atmosphere of 0.1 to 2.0 MPa.

[0127] The material treated in the above steps was ground in a ball mill for 6 hours, and the energy required for the grinding was 70 kJ.

[0128] The rare earth permanent magnet powder in the embodiment of the present invention has better overall properties, further improved magnetic properties, higher density of the magnetic powder, and more uniform particle size distribution of the magnetic powder, compared with the conventional rare earth permanent magnet powder. Some advantages of the embodiment of the present invention over the conventional technology are described below with specific experimental data.

[0129] Table 1. Characteristics of magnetic powder JPEG2025512118000008.jpg83145

[0130] From the above, it is clear that the rare earth permanent magnet powder in the embodiment of the present invention has magnetic properties such as high maximum magnetic energy product, remanence, and intrinsic coercivity, and also has more uniform particle size distribution and compressed density. In addition, in the thermogravimetric analysis process, the weight increase is less than 3.2% at 400°C in an air atmosphere, which indicates that the rare earth permanent magnet powder can maintain good stability even in a high-temperature environment. Therefore, the rare earth permanent magnet powder has excellent overall properties. The overall properties (magnetic energy product) of the magnetic powder are improved, the particle size distribution is wide, the compressed density and coercivity are improved, and the loss of the magnetic powder after molding is reduced. Manufacturing of high density, low loss rare earth bonded magnets

[0131] Example 13 The high density rare earth permanent magnet powder produced in Example 6, polyamide resin (nylon 12), titanate coupling agent, diethylhexyl phthalate (DOP), silica and butylhydroxyanisole (BHA) were mixed to obtain a mixture. The ratio of polyamide resin (nylon 12), titanate coupling agent, diethylhexyl phthalate (DOP), silica and butylhydroxyanisole was 90:2:2:4:2, and the masses of polyamide resin (nylon 12), titanate, diethylhexyl phthalate (DOP), silica and butylhydroxyanisole and their ratios in the mixture are shown in Table 2.

[0132] The mixed pellets were heated to 200°C to melt, and then added to an injection molding machine with a magnetic field orientation of 8 kOe for injection molding to obtain a high density, low loss rare earth bonded magnet.

[0133] After that, the high-density, low-loss rare earth bonded magnets were subjected to an irreversible loss test (GB / T 40794-2021) under the condition of being kept at 120°C for 192 hours.

[0134] Table 2. Characteristics of high density, low loss rare earth bonded magnets JPEG2025512118000009.jpg48145

[0135] Example 14 The high density rare earth permanent magnet powder produced in Example 7, polyamide resin (nylon 12), titanate coupling agent, diethylhexyl phthalate (DOP), silica and butylhydroxyanisole (BHA) were mixed to obtain a mixture. Here, the ratio of polyamide resin (nylon 12), titanate coupling agent, diethylhexyl phthalate (DOP), silica and butylhydroxyanisole was 90:2:2:4:2, and the masses of polyamide resin (nylon 12), titanate coupling agent, diethylhexyl phthalate (DOP), silica and butylhydroxyanisole and their ratios in the mixture are shown in Table 3.

[0136] The mixed pellets were heated to 200°C to melt, and then added to an injection molding machine with a magnetic field orientation of 8 kOe for injection molding to obtain a high density, low loss rare earth bonded magnet.

[0137] After that, the high-density, low-loss rare earth bonded magnets were subjected to an irreversible loss test (GB / T 40794-2021) under the condition of being kept at 120°C for 192 hours.

[0138] Table 3. Characteristics of high density, low loss rare earth bonded magnets JPEG2025512118000010.jpg48144

[0139] Example 15 The high density rare earth permanent magnet powder produced in Example 6, thermoplastic elastomer (TPE), oleic acid, butylhydroxyanisole (BHA), and magnesium hydroxide were mixed to obtain a mixture. Here, the ratio of the thermoplastic elastomer (TPE), oleic acid, butylhydroxyanisole (BHA), and magnesium hydroxide was 88:6:4:2, and the masses of the thermoplastic elastomer (TPE), oleic acid, butylhydroxyanisole (BHA), and magnesium hydroxide and their ratios in the mixture are shown in Table 4.

[0140] The mixed pellets were heated to 180°C to melt, and then added to an injection molding machine with a magnetic field orientation of 8 kOe for injection molding to obtain a high density, low loss rare earth bonded magnet.

[0141] After that, the high density, low loss rare earth bonded magnets were subjected to flame retardancy tests and hardness tests.

[0142] Table 4. Characteristics of high density, low loss rare earth bonded magnets JPEG2025512118000011.jpg48149

[0143] Example 16 The high density rare earth permanent magnet powder produced in Example 6, nitrile rubber, titanate coupling agent, benzene polycarboxylic acid ester and oleic acid were mixed to obtain a mixture, in which the ratio of the nitrile rubber, titanate coupling agent, benzene polycarboxylic acid ester and oleic acid was 88:2:4:6. The masses of the nitrile rubber, titanate coupling agent, benzene polycarboxylic acid ester and oleic acid and their ratios in the mixture are shown in Table 5.

[0144] The mixture was produced as mixed pellets in a twin screw extruder.

[0145] The mixed pellets were heated to 80°C to melt, and then added to an injection molding machine with a magnetic field orientation of 8 kOe for injection molding to obtain a high density, low loss rare earth bonded magnet.

[0146] After that, the high-density, low-loss rare earth bonded magnets were subjected to an irreversible loss test (GB / T 40794-2021) under the condition of being kept at 120°C for 192 hours.

[0147] Table 5. Characteristics of high density, low loss rare earth bonded magnets JPEG2025512118000012.jpg48144

[0148] Example 17 The high density rare earth permanent magnet powder produced in Example 7, nitrile rubber, titanate coupling agent, benzene polycarboxylic acid ester and oleic acid were mixed to obtain a mixture, in which the ratio of the nitrile rubber, titanate coupling agent, benzene polycarboxylic acid ester and oleic acid was 88:2:4:6. The masses of the nitrile rubber, titanate coupling agent, benzene polycarboxylic acid ester and oleic acid and their ratios in the mixture are shown in Table 6.

[0149] The mixture was produced as mixed pellets in a twin screw extruder.

[0150] The mixed pellets were heated to 80°C to melt, and then added to an injection molding machine with a magnetic field orientation of 8 kOe for injection molding to obtain a high density, low loss rare earth bonded magnet.

[0151] After that, the high-density, low-loss rare earth bonded magnets were subjected to an irreversible loss test (GB / T 40794-2021) under the condition of being kept at 120°C for 192 hours.

[0152] Table 6. Characteristics of high density, low loss rare earth bonded magnets JPEG2025512118000013.jpg48145

[0153] Example 18 The high density rare earth permanent magnet powder produced in Example 7, thermoplastic elastomer (TPE 50% + TPU 50%), oleic acid, butyl hydroxyanisole (BHA), and magnesium hydroxide were mixed to obtain a mixture. Here, the ratio of the thermoplastic elastomer (TPE 50% + TPU 50%), oleic acid, butyl hydroxyanisole (BHA), and magnesium hydroxide was 70:5:20:5, and the masses of the thermoplastic elastomer (TPE 50% + TPU 50%), oleic acid, butyl hydroxyanisole (BHA), and magnesium hydroxide and their ratios in the mixture are shown in Table 7.

[0154] The mixture was produced as mixed pellets in a twin screw extruder.

[0155] The mixed pellets were heated to 150°C to melt them, and then added to an injection molding machine with a magnetic field orientation of 8 kOe for injection molding to obtain a high density, low loss rare earth bonded magnet.

[0156] After that, the high density, low loss rare earth bonded magnets were subjected to flame retardancy tests and hardness tests.

[0157] Table 7. Characteristics of high density rare earth permanent magnet powder JPEG2025512118000014.jpg48145

[0158] From the above, it can be seen that in the present invention, even when the magnetic field strength is reduced, the produced high density and low loss rare earth bonded magnet has good comprehensive properties, which effectively improves the comprehensive properties of the rare earth bonded magnet and reduces the magnetic field strength requirement of the manufacturing process of the rare earth bonded magnet, thereby reducing the manufacturing cost of the rare earth bonded magnet to a certain extent, and enabling the rare earth bonded magnet to be successfully applied in the traditional commercial application environment.

[0159] As used herein, the terms "one embodiment," "an embodiment," or "one or more embodiments" mean that a particular feature, structure, or characteristic described in connection with an embodiment is included in at least one embodiment of the present application. Note that instances of the phrase "in one embodiment" are not necessarily all referring to the same embodiment.

[0160] In the specification provided herein, many specific details are described. However, it is understood that embodiments of the present application can be practiced without these specific details. In some instances, well-known methods, structures and techniques have not been shown in detail in order not to obscure an understanding of this specification.

[0161] In the claims, any reference signs placed between parentheses shall not limit the scope of the claim. The word "comprise" does not exclude the presence of elements or steps not stated in the claim. The word "a" or "one" preceding an element does not exclude the presence of a plurality of such elements. The application can be realized by means of hardware comprising several different elements, and by means of a suitably programmed computer. In a claim enumerating several devices, several of these devices may be embodied by one and the same hardware. The use of words such as first, second and third does not indicate any order. These words can be interpreted as names.

[0162] It should be noted that the above examples are only used to explain the technical solutions of the present application, and are not intended to limit the same. Although the present application has been described in detail with reference to the above examples, those skilled in the art should understand that the technical solutions described in the above examples may be modified or some of the technical features may be replaced with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. Molecular formula is Sm x Fe 100-x-y-z M y I z (wherein 6.0≦x≦9.5, 0≦y≦13, 1≦z≦15.2, M is a 3d transition metal and / or a 4d transition metal, and I is an interstitial atom, including N or a combination of N and H), the maximum magnetic energy product is 36.299 MGOe or more, and the pressed density is 5.5 g / cm 3 The high density rare earth permanent magnet powder is characterized by the above.

2. 2. The high density rare earth permanent magnet powder according to claim 1, wherein the 3d transition metals and / or 4d transition metals include one or more of Ti, V, Cr, Mn, Co, Ni, Cu, Zn, Zr, Nb, and Mo.

3. 2. The high density rare earth permanent magnet powder according to claim 1, characterized in that the particle size is within the ranges 0.6 μm≦x10≦0.92 μm, 2 μm≦x50≦2.55 μm, and 5.93 μm≦x99≦8.1 μm.

4. 2. The high density rare earth permanent magnet powder according to claim 1, characterized in that the powder has a residual magnetic induction strength of 14.289 kGs or more and an intrinsic coercivity of 10.255 kOe or more.

5. 2. The high density rare earth permanent magnet powder according to claim 1, which has a weight increase rate of less than 3.2% in thermogravimetric analysis at 400° C. in an air atmosphere.

6. A method for producing high density rare earth permanent magnet powder according to any one of claims 1 to 5, obtaining a raw material, the raw material containing Sm, Fe, and a 3d transition metal and / or a 4d transition metal, the ratio of Sm, Fe, and the 3d transition metal and / or the 4d transition metal in the raw material being the same as the ratio of each element in the high density rare earth permanent magnet powder; producing a samarium-iron master alloy using the raw material; The samarium-iron alloy is reacted with nitrogen or a mixture of nitrogen and hydrogen gas to produce the samarium-iron-nitrogen alloy Sm x Fe 100-x-y-z M y I z forming a grinding the samarium-iron-nitrogen alloy to obtain the high density rare earth permanent magnet powder.

7. The step of producing a samarium-iron master alloy using the raw material includes:

5. The method of claim 4, comprising the step of producing a samarium-iron master alloy by rapid solidification flake technology using said feedstock.

8. 8. The method according to claim 7, wherein in the step of using the raw material to produce the samarium-iron master alloy by the rapid solidification flake technique, the rotation speed of the rapid solidification roll is 50-80 m / s, and the thickness of the produced samarium-iron master alloy is less than 1 mm.

9. The method according to claim 4, wherein in the gas-solid reaction process, the reaction temperature is 400-800°C, the reaction time is 1-200 hours, and the pressure is 0.1-2.0 MPa.

10. 5. The method of claim 4, wherein the total energy output in the polishing process is 60-80 KJ.

11. 6. A high density, low loss rare earth bonded magnet, produced using the high density rare earth permanent magnet powder according to any one of claims 1 to 5, an adhesive, and a processing aid.

12. 2. The high density, low loss rare earth bonded magnet of claim 1, wherein the adhesive comprises at least one of chlorinated polyethylene, polyamide resin, thermoplastic polyimide, liquid crystal polymer, polyphenylene sulfide, polyphenylene ether, polyolefin, modified polyolefin, polycarbonate, polymethyl methacrylate, polyether, polyether ketone, polyetherimide, polyformaldehyde, and chlorosulfonated polyethylene, and / or at least one of copolymers, blends, and polymer alloys formed with at least one of chlorinated polyethylene, polyamide resin, thermoplastic polyimide, liquid crystal polymer, polyphenylene sulfide, polyphenylene ether, polyolefin, modified polyolefin, polycarbonate, polymethyl methacrylate, polyether, polyether ketone, polyetherimide, polyformaldehyde, and chlorosulfonated polyethylene.

13. 12. The high density, low loss rare earth bonded magnet of claim 11, wherein the adhesive comprises a thermoplastic elastomer.

14. 12. The high density, low loss rare earth bonded magnet according to claim 11, wherein the processing aid comprises at least one of a coupling agent, a plasticizer, a lubricant, and a flame retardant.

15. 15. The high density, low loss rare earth bonded magnet according to claim 14, wherein the coupling agent comprises a titanate-based coupling agent and / or a silane-based coupling agent.

16. 15. The high density, low loss rare earth bonded magnet of claim 14, wherein the plasticizer comprises at least one of dioctyl phthalate (DOP), stearates, fatty acids, phosphoric esters, benzene polycarboxylic esters, and alkyl sulfonic esters.

17. 5. The high density, low loss rare earth bonded magnet according to claim 4, wherein the lubricant contains at least one of silicone oil, wax, fatty acid, oleic acid, polyester, synthetic ester, carboxylic acid, alumina, silica, and titanium dioxide.

18. A method for producing a high density, low loss rare earth bonded magnet according to any one of claims 11 to 17, Mixing high density rare earth permanent magnet powder, an adhesive, and a processing aid to obtain a mixture; and processing the mixture by an extrusion or injection molding process in a magnetic field orientation exceeding 8 kOe to produce a high density, low loss rare earth bonded magnet.

19. processing the mixture by an extrusion or injection molding process in an environment where the magnetic field orientation exceeds 8 kOe to produce a high density, low loss rare earth bonded magnet; The method according to claim 8, characterized in that when using an extrusion molding process, the method includes the steps of kneading the mixture in a kneader, heating the mixture to melt it, then injecting it into a single screw extruder with a magnetic field orientation of more than 8 kOe, extruding it through the single screw extruder, and then cooling and molding it to obtain a high density and low loss rare earth bonded magnet.

20. processing the mixture by an extrusion or injection molding process in an environment where the magnetic field orientation exceeds 8 kOe to produce a high density, low loss rare earth bonded magnet; When using an injection molding process, the mixture is produced as mixed pellets in a twin screw extruder; 20. The method of claim 18, further comprising the steps of: heating the mixed pellets to melt them, and then injecting them into an injection molding machine with a magnetic field orientation of more than 8 kOe to obtain a high density, low loss rare earth bonded magnet.

Citation Information

Patent Citations

  • A submicron anisotropic samarium iron nitrogen magnet powder and a method for preparing a hybrid bonded magnet therefrom

    CN106312077A

  • Manufacturing method for rare earth magnet powder and rare earth bond magnet

    JP2004363531A

  • Compound magnetic powder for bond magnet, resin composition for bond magnet, and bond magnet

    JP2007035667A

  • Anisotropic coupling magnet and manufacturing method thereof

    JP2021190706A